Metabolic and transcriptional responses to starvation are regulated by FOXO in the red flour beetle, Tribolium castaneum. (21st April 2022) - Zhang, Nan; Meng, Xiangkun; Jiang, Heng; Ge, Huichen; Zheng, Yang; Qian, Kun; Wang, Jianjun
Abstract: Intermittent food scarcity is commonly encountered in all organisms including insects. Although the forkhead box O (FOXO) transcription factor is a well‐known component of signalling cascades related to starvation stress, the detailed regulatory mechanisms during long‐term starvation remain poorly understood in insects. In the present study, using the red flour beetle, Tribolium castaneum, as a model organism, we showed that starvation treatment increased the expression of FOXO at both mRNA and protein levels and promoted its nuclear translocation to activate its transcriptional activity. Knockdown of FOXO leads to a significant reduction in the lifespan of T . castaneum accompanying reduced glycogen and triglyceride depletion as well as decreased glucose and trehalose accumulation under starvation conditions. Consistently, expression patterns of genes involved in gluconeogenesis, glycogenolysis and trehalose metabolism under starvation conditions were significantly affected in dsFOXO‐injected beetles. These results provided evidence that FOXO played an important role in the tolerance to prolonged starvation by regulating metabolic and transcriptional responses. Abstract : Starvation induces FOXO expression and nuclear translocation in Tribolium castaneum FOXO functions in starvation tolerance. FOXO regulates metabolic and transcriptional responses to starvation stress.